Engineering Design of A Gang Drilling Machine Equipped with Jig and Fixtures to Make A Prototype Machine in Birdcage Production - Widiyono, Eddy; Winarto; Wardhani, Rivai; Rusdiyana, Liza (IPTEK The Journal for Technology and Science, 2025)
This paper is dealing with the engineering design of a gang drilling machine with jig & fixtures to make a prototype machine. This effort has been done in order to solve the problem which aroused in small business enterprises producing birdcages. The problem was how to minimize the production time in making a lot of holes that have same distance and straightness. Hopefully, the prototype machine can help the small business enterprises to increase their production rate.The design engineering process has been carried out by variant approximation on dowel pin modular fixtures in order to simplify fixtures design. CAD CAM software has also been used as fixtures synthesized method including geometric analysis and three dimensional fixtures assembling. The resulting prototype machine can be well operated and based on the running test, it can be concluded that the greater the motor rotation the greater the power needed. As for teak wood, at 250 rpm motor rotation the power needed is 26.5 watt, and at 400 rpm the motor needs power of 43.6 watt while at 600 rpm the motor needs power of 600 watt. The power consumption is also depends on the type of material, the better the mechanical properties of the materials, the higher the power consumption. For cast iron, the 400 rpm motor rotation needs power as high as 569.7 watt. This prototype of gang drilling machine needs power of 350 watt to make five holes on teak wood while ordinary drilling machine needs total power of 1350 watt.